(untitled) - McCabe, James D. (San Francisco, Calif., 1998)
Powerful, mission-critical networks that carry real-time applications, multimedia, or just heavy traffic are increasingly complex and costly to build. Design decisions based on insufficient or flawed analysis can have drastic consequences in both efficiency and expense. Practical Computer Network Analysis and Design prepares you to make the best decisions by applying sound, tested design principles to your network and considering the system-wide effects of each decision. The author provides a step-by-step process for analyzing user requirements, visualizing the network structure in terms of traffic flows, and doing quantitative measurements. Once you have a clear, scientifically based picture of you network environment, he guides you in developing strategies for routing, addressing, security, and network management and then in choosing and integrating technologies to realize your plan.
Keywords: Mạng máy tính,Computer networks; Cấu trúc và thiết kế,Design and construction